NITROGEN TRANSFORMATION AS AFFECTED BY APPLICATION OF NITROGEN, VERMICOMPOST AND HERBICIDE ( , VERMICOMPOST AND HERBICIDE (CLODINAFOP PROPARGYL) IN SANDY SOIL - SINGH SHEORAN, HARDEEP; B. S. , DUHAN; SUNITA SHEORAN, K. S. GREWAL AND (The Bioscan, 2016)
Application of Nitrogen (N) @ 100 and 200 mg kg-1 soil significantly increased the NH4 +-N and NO3 - -N contents in soil, respectively over control. NH4 +-N increased from 9.10 to 39.25 and 59.70 mg kg-1 soil respectively (14th day) and was the peak observed whereas NO3 - -N contents increased from 11.74 to 86.79 and 104.66 mg kg-1 soil respectively (peak value) on the 56th day of incubation. Addition of vermincompost at 1% significantly increased the NH4 +-N and peak was found on 14th day and the increase was from 15.76 to 58.48 mg kg-1 soil. Moreover in case of NO3 - -N contents increase was from9.79 to 65.87 mg kg-1 soil (peak value) on the 56th day of incubation. Effect of nitrogen at both the levels (100 and 200 mg kg-1) was not spectacular on NO2 - -N contents in soil except from 3rd to 7th day of incubation where increase was from 0.16 to 2.56 and to 3.23 mg kg-1 on 3rd and from 0.17 to 2.05 to 2.74 mg kg-1 soil on 7rd day of incubation respectively . However, addition of herbicide in soil significantly decreased the NH4 +-N, NO3 - -N and NO2 - -N contents at all incubation periods.